Comparative review of Francisella tularensis and Francisella novicida - Kingry, Luke C.; Petersen, Jeannine M. (Frontiers in Cellular and Infection Microbiology, 2014)
Francisella tularensis is the causative agent of the acute disease tularemia. Due to its extreme infectivity and ability to cause disease upon inhalation, F. tularensis has been classified as a biothreat agent. Two subspecies of F. tularensis, tularensis and holarctica, are responsible for tularemia in humans. In comparison, the closely related species F. novicida very rarely causes human illness and cases that do occur are associated with patients who are immune compromised or have other underlying health problems. Virulence between F. tularensis and F. novicida also differs in laboratory animals. Despite this varying capacity to cause disease, the two species share ~97% nucleotide identity, with F. novicida commonly used as a laboratory surrogate for F. tularensis. As the F. novicida U112 strain is exempt from U.S. select agent regulations research studies can be carried out in non-registered laboratories lacking specialized containment facilities required for work with virulent F. tularensis strains. This review is designed to highlight phenotypic (clinical, ecological, virulence and pathogenic) and genomic differences between F. tularensis and F. novicida that warrant maintaining F. novicida and F. tularensis as separate species. Standardized nomenclature for F. novicida is critical for accurate interpretation of experimental results, limiting clinical confusion between F. novicida and F. tularensis and ensuring treatment efficacy studies utilize virulent F. tularensis strains.